PENGARUH PACKAGING, SOSIAL MEDIA FACEBOOK, BRAND IMAGE, KUALITAS PELAYANAN, WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN - abdul wakilul akbar (Universitas Mahendradatta Denpasar, 2023)
The amount of company competition and the current pandemic situation forces every producer to be smart in choosing products to produce by carrying out various innovations and promotions, one of which is Ohadoku, which is food that carries a retro style. This type of research uses associative research with a total of 110 samples from all ohadoku consumers in Uma Ilopeta. The sampling technique used purposive sampling with the results of the t-test significance analysis, namely x₁ 0.034, x₂ 0.006, x₃ 0.022, x₄ 0.030, x₅ 0.002 while the significance result of the f test is 0.000 which indicates that all independent variables have a significant effect on the dependent variable.